GREEN CENTRAL BANKING: A NEW ROLE FOR THE CENTRAL BANKS IN THE FINANCIAL SYSTEM - Omer Faruk Tekdogan (Bank Indonesia, 2023)
The financial sector has a key role to play in the transition to a more sustainable and low-carbon economy. Being major actors in the financial system, central banks can exert influence to encourage the adoption of green finance and reduce risks associated with climate change. A novel idea called